(3QSGdI aj SbWGJ GdYhGes - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s ((3YHO GdaJGM Hf MSf Hf eMehO Hf CMeO Hf MSf GdehUdi s)
(3ChdgG (B:s
(3afbhd eeG jLH Cf jYde eG jfHZi Cf jJLfH Yfg ef GdCdaGX CbSGe bSe LhRI HYV Cgd GddSGf eWdbG Ch ai MGd ef GdCMhGd s
(3BNQgG (B:s
(3hefgG GdfcGJ , HcSQ Gdfhf LeY fcJg , hZPG VeJ GdfhGf MPaJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3HMhGTjgG JYdjbGJ heTQhMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs